Looking Forward, Looking Back: British Journal of Management 2000–2015 - Goergen, Marc; Evanschitzky, Heiner (Wiley, 2018)
This paper reflects on the past 16 years of the British Journal of Management (BJM) and discusses what the future holds. The paper analyses publication statistics and submission figures, as well as Special Interest Group (SIG) affiliation of submissions over the more recent period of 2007 to 2015. We find that human resource management (HRM) has a clear dominance among the SIGs. Other fields that are well represented include strategy, work psychology, corporate governance and performance management. We also highlight that submissions to the BJM are predominantly made by UK-based authors, possibly reflecting the concentration of UK-based academics among the pool of associate editors and the editorial board members. Finally, we look forward by suggesting potential areas of interest for new submissions in the areas of Marketing & Retailing, Corporate Finance, and Corporate Governance, capitalising on areas of strength as well as areas in line with the cross-disciplinary nature of the BJM.
Keywords: Bibliographic analysis; Publication characteristics; Future outlook; Editorial; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura; ODS 4 - Educación de calidad